Therapeutic potential and action mechanisms of licochalcone B: a mini review - Shaikh, Sibhghatulla; Lee, Eun Ju; Ahmad, Khurshid; Choi, Inho (Frontiers in Molecular Biosciences, 2024)
Licochalcone B (LicB), a chalcone derived from Glycyrrhiza uralensis and Glycyrrhiza glabra, has received considerable attention due to its diverse pharmacological properties. Accumulated data indicates that LicB has pharmacological effects that include anti-cancer, hepatoprotective, anti-inflammatory, and neuroprotective properties. The action mechanism of LicB has been linked to several molecular targets, such as phosphoinositide 3-kinase/Akt/ mammalian target of rapamycin, p53, nuclear factor-κB, and p38, and the involvements of caspases, apoptosis, mitogen-activated protein kinase-associated inflammatory pathways, and anti-inflammatory nuclear factor erythroid 2-related factor 2 signaling pathways highlight the multifaceted therapeutic potential of LicB. This review systematically updates recent findings regarding the pharmacological effects of LicB, and the mechanistic pathways involved, and highlights the potential use of LicB as a promising lead compound for drug discovery.